Socio-economic consequences of mental distress: quantifying the impact of self-reported mental distress on the days of incapacity to work and medical costs in a two-year period$da longitudinal study in Germany - Müller, Gerhard; Bombana, Manuela; Heinzel-Gutenbrunner, Monika; Kleindienst, Nikolaus; Bohus, Martin; Lyssenko, Lisa; Vonderlin, Ruben (BMC public health, 2021)
Mental disorders are related to high individual suffering and significant socio-economic burdens. However, it remains unclear to what extent self-reported mental distress is related to individuals’ days of incapacity to work and their medical costs. This study aims to investigate the impact of self-reported mental distress for specific and non-specific days of incapacity to work and specific and non-specific medical costs over a two-year span.
Gesehen am 17.05.2021